Lichen sclerosus and the association with subsequent psychiatric disorders - Alfarsi, Salam; Recke, Andreas; Bieber, Katja; Thaçi, Diamant; Ludwig, Ralf J.; Curman, Philip (Frontiers in Medicine, 2025)
BackgroundLichen sclerosus (LS) is an acquired, non-communicable, chronic inflammatory disease that predominantly affects the genital area and may lead to substantial impairment in quality of life. While some studies reported elevated rates of depression and anxiety among patients with LS, the available evidence is limited by often small sample sizes, cross-sectional designs, narrow matching, and limited consideration of sex- or race-disparities. Moreover, the risk of a broader spectrum of psychiatric disorders remains insufficiently characterized.ObjectiveTo evaluate the risk of a larger spectrum of psychiatric disorders following a diagnosis of LS in a retrospective cohort study.MethodsThe US Collaborative Network of TriNetX was used to create a propensity-score-matched cohort of individuals with LS and non-LS controls (n = 42,581 per cohort). Risk of psychiatric disorders following the index events was analyzed in a retrospective cohort study. Several sensitivity analyses were conducted to assess robustness of the findings. Subgroup analyses were performed to identify potential sex- or racial-disparities.ResultsWithin 5 years, 3.92% of patients with LS as opposed to 3.43% of controls were subsequently diagnosed with a depressive episode (HR 1.31, CI 1.22–1.40, p < 0.0001). Furthermore, risks of recurrent major depression (HR 1.71, CI 1.48–1.98, p < 0.0001) and reaction to severe stress (HR 1.62, CI 1.45–1.80, p < 0.0001) were increased in patients with LS. These risks seemed more pronounced in those of White ethnicity and in women. Risks for suicidal ideations, suicide attempts, and schizophrenia were not different between patients and matched controls.ConclusionPatients with LS are at a moderately increased risk of depression and stress-related psychiatric disorders.